2004
DOI: 10.1038/sj.bjc.6601897
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiangiogenesis therapy with marimastat, captopril and fragmin in patients with advanced cancer

Abstract: Marimastat, low molecular weight heparins and captopril have antiangiogenic activity in vitro and in animal models. We studied the safety and efficacy of the combination of these drugs in patients with advanced cancer. In all, 50 patients were enrolled. Captopril was given orally at a dose of 50 mg bd daily. Fragmin was administered as a daily subcutaneous injection of 200 units kg À1 for the first 28 days and 5000 units thereafter. Marimastat was given at 10 mg bd orally. Serum, plasma and urinary angiogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…The catalytic domain of human TACE was expressed and purified by using reported protocols (23). Fluoregenic peptide QF-45 [Mca-Ser-Pro-Leu-Ala-Gln-Ala-Val-Arg-SerSer-Ser-Arg-Lys(Dnp)-NH 2 ] was synthesized at the Weizmann Institute core facilities.…”
Section: Methodsmentioning
confidence: 99%
“…The catalytic domain of human TACE was expressed and purified by using reported protocols (23). Fluoregenic peptide QF-45 [Mca-Ser-Pro-Leu-Ala-Gln-Ala-Val-Arg-SerSer-Ser-Arg-Lys(Dnp)-NH 2 ] was synthesized at the Weizmann Institute core facilities.…”
Section: Methodsmentioning
confidence: 99%
“…A combination therapy of an ACEI, a matrix metalloprotease inhibitor and a low molecular-weight heparin was tested in 50 patients with various advanced malignancies including lung cancer and showed some anticancer activity (Jones et al 2004). Uemura et al (2008) proposed activity of ARB in prostate cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that COX-2 overexpression has a significantly central role to in cancer development by promoting cell proliferation, decreasing apoptosis rate, and increasing invasive and metastatic potential of the primary tumor [3739]. To clarify the mechamism of CS-6 from Chansu used as an anti-cancer agent, we investigated whether COX-2 plays an important role in CS-6 bioactive function, and found CS-6 could inhibit COX-2 expression, along with inhibiting NSCLC viability, migration and colony formation.…”
Section: Discussionmentioning
confidence: 99%